Chemotherapy-Induced ECM Remodeling in Triple-Negative Breast Cancer - Fatherree, Jackson. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisor: Madeleine Oudin.; Committee: Philip Hinds, Charlotte Kuperwasser, and Lauren Black.; Keywords: Oncology, and Biomedical engineering.